Pelaksanaan Supervisi Klinis Kepala Sekolah Pendidikan Anak Usia Dini Islam Terpadu Kota Bengkulu (Studi Deskriptif Kualitatif di PAUD IT Auladuna Kota Bengkulu) - Uci Pranita; Nina Kurniah; Anni Suprapti (Jurnal Ilmiah POTENSIA, 2018)
This study aims to describe the planning of clinical supervision program, stages of clinical supervision implementation, and supporting factors and inhibiting the implementation of clinical supervision in early childhood IT Auladuna Bengkulu City. The method used is descriptive qualitative. Techniques of collecting data through interviews, observation and documentation. Data analysis techniques use interactive models, including: data collection, data reduction, data presentation, and conclusions. Examination of data in this research is done by triangulation of data. The results showed (1) Implementation of principal clinical supervision begins with planning of clinical supervision program and make schedule of supervision. (2) The implementation of clinical supervision is carried out with the initial planning stage, the class observation stage, the reverse meeting stage (reverse discussion). (3) Supporting factors for the implementation of clinical supervision: a) to help overcome the learning problems faced by teachers, b) improve teacher's teaching ability, c) the supervision program created by the principal. Inhibiting factors are: a) the time of clinical supervision has been established but there are other agendas in the school so the implementation should be canceled, b) usually the teacher will be in supervision feel tense so there must be good preparation so that later get good results, c) teachers sometimes feel less ready and disturbed because not yet accustomed supervised clinical.